The Urgency of Character Education in the Era of the Industrial Revolution 4.0: A Review from a Philosophical Perspective - Harahap, Annisa Adinda Putri; Herlambang, Yusuf Tri (Jurnal Ilmiah Global Education, 2025)
This study aims to explore the urgency of character education in the Industrial Revolution 4.0 era, characterized by the rapid development of digital technologies such as artificial intelligence, the Internet of Things (IoT), and big data. These changes provide significant opportunities for educational innovation, but also give rise to new challenges, such as the degradation of students' character and the dominance of technical skills over moral values. Using a qualitative approach using literature study methods, this study analyzes theories, concepts, and research findings related to character education in the global and Indonesian contexts. The results show that character education is a key element in preparing the younger generation to face the social and ethical challenges presented by technology. Integrating values ​​such as honesty, responsibility, empathy, and digital ethics into the curriculum is crucial for shaping individuals who are not only technically skilled but also possess a solid moral foundation. Character education acts as a moral bulwark that helps students overcome the negative impacts of technology, such as digital addiction and data misuse. In conclusion, character education should not be merely an addition to the curriculum, but must become a central pillar in shaping a generation ready to compete globally while upholding noble values. In the face of rapid change, character education must be strategically designed to strengthen individual moral identity and promote social harmony in the digital era.